Unlocking Financial Success: How Literacy and Inclusion Shape SME Owners' Well-Being in Makassar - Pabane, Wulan; Todingbua, Manuel August; Mongan, Claudio Julio (Master of Management Study Program, Universitas Kristen Indonesia Paulus, 2025)
Financial literacy and financial inclusion play a crucial role in ensuring the financial well-being of small and medium enterprise (SME) owners. This study aims to analyze the impact of financial literacy and financial inclusion on the financial well-being of SME owners in Makassar, Indonesia. Using a quantitative approach, data were collected from 96 SME owners through structured questionnaires. The research model was tested using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to assess the relationships among variables. The findings reveal that both financial literacy and financial inclusion have a positive and significant impact on the financial well-being of SME owners. However, financial literacy exerts a stronger influence compared to financial inclusion. The results highlight the importance of improving financial knowledge and expanding access to financial services to enhance SMEs' financial stability and growth. The study contributes to the literature by providing empirical evidence on the relationship between financial literacy, financial inclusion, and financial well-being in the SME sector. Policymakers and financial institutions should implement targeted programs to strengthen financial literacy and promote inclusive financial systems to support SME sustainability.